How do Brands compare from the perspectives of the CBBE model: A Comparative study of a Local and International Brand in Nigeria - Adeyemi, Ayotunde Mary; Boolaky, Mehraz; Gungaphul, Mridula (Journal of Research in Marketing (ISSN: 2292-9355), 2017)
The CBBE (Consumer Based Brand Equity) model has been invariably used to evaluate the performance of brands in different types of products such as tourism, etc. Not much has been done to compare how brands fare using the model as a theoretical framework. The aim of this paper is to examine the role that the CBBE model plays in comparing a specific local product with an international product in the Nigerian sugar sector.The study draws on primary data collected from two group interviews and a survey of 166 students of both Rufus Giwa Polytechnic and Federal University of Technology in Ondo State Nigeria and is part of a broader study (dissertation) conducted by the main author. University students were chosen for this study as this group are prime users of sweeteners and are at a stage where they are forming brand adoption decisions on their own.The study finds that distribution is a primary salience tool for both Saint Louis and Dangote. This is done by placing the brands in stores and markets the target customer will frequent. Relevance is maintained by the provision of need fulfilling products that equate price to perceived quality. Thus, due to the affordability of Dangote, it was more purchased by the research population. Nonetheless, there was a higher sense of emotional loyalty to Saint Louis. The study recommends that product brands use distribution as promotion to their target customer, while ensuring that they anticipate customer needs and eliminate barriers to adoption. Need fulfilment may encourage frequency of purchase and use, but for better resonance, positive feelings need to be encouraged in brand messaging.